How can you persuade me online? The impact of goal-driven motivations on attention to online information. (April 2020) - Taylor, Sarah; Graff, Martin; Taylor, Rachel
Abstract: Individuals are increasingly using the internet to communicate online with many of their interactions being persuasive. Whilst there is some evidence to suggest that persuasion can occur online it is still unclear as to the underlying mechanisms driving this process. The current study aims to address this by examining individuals' attention to, and motivations to process, online information. To achieve this, an information recall paradigm was adopted whereby an undergraduate student sample (n = 91) were asked to recall information which had been presented to them in pre-scripted personally-relevant scenarios. Results identified that peripheral (e.g. contextual) cues activated goal-driven motivations significantly increasing attention to message content (i.e. central information) when personal benefits were implied. Conversely, when personal costs were implied these effects were reversed and information processing significantly attenuated. These results serve to reinforce the notion that online information processing is motivated by goal-driven behaviour and are the first to identify how goals impact on information processing. The findings have implications for both organisations and individuals who use the internet for persuasive purposes (e.g. political campaigning) and are discussed in relation to the dominant theories of persuasion and how they can explain online persuasion. Highlights: Online persuasive information processing is motivated by goal-driven behaviour. Attention to message content occurs when goal attainment evidence is conveyed. Contextual cues activate goal-driven motivations for online information processing. Personal benefits implied by contextual cues increase attention to message content. Personal costs implied by situational cues attenuate persuasive message processing.